Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1051/0004-6361/201731316
|View full text |Cite
|
Sign up to set email alerts
|

SOLAR-ISS: A new reference spectrum based on SOLAR/SOLSPEC observations

Abstract: Context. Since April 5, 2008 and up to February 15, 2017, the SOLar SPECtrometer (SOLSPEC) instrument of the SOLAR payload on board the International Space Station (ISS) has performed accurate measurements of solar spectral irradiance (SSI) from the middle ultraviolet to the infrared (165 to 3088 nm). These measurements are of primary importance for a better understanding of solar physics and the impact of solar variability on climate. In particular, a new reference solar spectrum (SOLAR-ISS) is established in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 31 publications
2
80
0
Order By: Relevance
“…Therefore, every emitted photon from the coronal ions will originate from a very recent photo-absorption, and the total number of photons emitted per unit time will be given by equation 3 for any coronal ion emission line that ends in the ground state. (Meftah et al, 2018). Bottom: Relative rate of photo excitation and spontaneous emission versus wavelength for any energy level transition based on the energy density from the top curve (scaled to 1 R ) as shown in the example in Section 3.2.2.…”
Section: Electron Temperaturementioning
confidence: 99%
“…Therefore, every emitted photon from the coronal ions will originate from a very recent photo-absorption, and the total number of photons emitted per unit time will be given by equation 3 for any coronal ion emission line that ends in the ground state. (Meftah et al, 2018). Bottom: Relative rate of photo excitation and spontaneous emission versus wavelength for any energy level transition based on the energy density from the top curve (scaled to 1 R ) as shown in the example in Section 3.2.2.…”
Section: Electron Temperaturementioning
confidence: 99%
“…The red curve is here for comparison. It is a calibrated solar spectrum taken at the ISS by Meftah et al (2018). The grey zone around the red curve represents the area covered by its error bars.…”
Section: Photometric Calibrationmentioning
confidence: 99%
“…The 15 solar irradiance models listed in Table 2 were used in the numerical simulations. Descriptions of each irradiance model can be found elsewhere [39][40][41][42][43][44][45][46][47][48][49]. A previous analysis of actual data concluded that primary sources of uncertainties in the solar irradiance models would be the instrument calibration uncertainties, which would be 2-3% in the solar reflective range [43].…”
Section: Solar Irradiance Modelsmentioning
confidence: 99%